Optimizing Generic Science Skills on the Concept of Reaction Rate Through Integration of Vak Strategies: A Comparative Analysis of Learning Effectiveness - Yenni Kurniawati; Hazilah Fakhraini; Adia Heriana Putri; Veni Rafni (Journal of Educational Chemistry (JEC), 2026)
The topic of reaction rates is considered difficult to teach to eleventh-grade science students because it is abstract and requires strong logical reasoning as well as well-developed observational skills. This study aimed to examine the effect of the Visualization Auditory Kinesthetic (VAK) learning model on students’ generic science skills in reaction rate material. A quantitative approach with an experimental design was employed. The results showed that the VAK learning model had a statistically significant effect on students’ generic science skills, as indicated by the t-test result (t = 4.562 > ttable = 1.998 at α = 0.05). Among the assessed indicators, direct observation showed the most significant improvement, achieving the highest average score of 90%. This was followed by indirect observation (87%), causal reasoning (83%), modeling (80%), and abstraction (75%). These findings indicate that the VAK learning model is particularly effective in enhancing students’ observational abilities in learning abstract chemistry concepts. Therefore, the VAK model is recommended as an alternative instructional approach in chemistry learning.